New species of Prolachesilla Mockford & Sullivan (Psocodea: ‘Psocoptera’: Lachesillidae: Graphocaeciliini) from Bolivia and Mexico - Arango, Stephania Sandoval; Obando, Ranulfo González; Aldrete, Alfonso Neri García (Zootaxa, 2017)
The genus Prolachesilla Mockford & Sullivan presently includes nine species, all described when the genus was erected; since then, no other species have been discovered. Here, we describe and illustrate one Bolivian and three Mexican species. This is the first record of Prolachesilla from Bolivia. A key to the species of the genus is included.